Conventional and High-Speed Intravital Multiphoton Laser Scanning Microscopy of Microvasculature, Lymphatics, and Leukocyte-Endothelial Interactions - Timothy P. Padera; Brian R. Stoll; Peter T.C. So; Rakesh K. Jain (Molecular Imaging)
The ability to determine various functions of genes in an intact host will be an important advance in the postgenomic era. Intravital imaging of gene regulation and the physiological effect of the gene products can play a powerful role in this pursuit. Intravital epifluorescence microscopy has provided powerful insight into gene expression, tissue pH, tissue pO 2 , angiogenesis, blood vessel permeability, leukocyte-endothelial (L-E) interaction, molecular diffusion, convection and binding, and barriers to the delivery of molecular and cellular medicine. Multiphoton laser scanning microscopy (MPLSM) has recently been applied in vivo to overcome three drawbacks associated with traditional epifluorescence microscopy: (i) limited depth of imaging due to scattering of excitation and emission light; (ii) projection of three-dimensional structures onto a two-dimensional plane; and (iii) phototoxicity. Here, we use MPLSM for the first time to obtain high-resolution images of deep tissue lymphatic vessels and show an increased accuracy in quantifying lymphatic size. We also demonstrate the use of MPLSM to perform accurate calculations of the volume density of angiogenic vessels and discuss how this technique may be used to assess the potential of antiangiogenic treatments. Finally, high-speed MPLSM, applied for the first time in vivo, is used to compare L-E interactions in normal tissue and a rhabdomyosarcoma tumor. Our work demonstrates the potential of MPLSM to noninvasively monitor physiology and pathophysiology both at the tissue and cellular level. Future applications will include the use of MPLSM in combination with fluorescent reporters to give novel insight into the regulation and function of genes.